2019
DOI: 10.35631/ijepc.4320029
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Organizational Citizenship Behaviour Among Public / Civil Employees: A Scoping Review

Abstract: Organizational citizenship behavior (OCB) throughout literature provides evidence in increasing organizational welfares as well as its employees’ welfares. It is important to understand the reasons behind the occurrence of OCB in order to increase the likelihood of employees to engage in OCB. Moreover, it is important for public/ civil employees to engage in OCB as they provide services to meet societal needs and demands. The present article set out to analyze the existing literature on the OCB’s antecedents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Referred to as "going beyond the call of duty" or "esprit de corps" (Bolino and Turnley, 2003), OCB is initially defined as "individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system and that in aggregate promotes the effective functioning of the organization" (Organ, 1988, p. 4). Results of previous studies have suggested that, for any organization to function efficiently, it must of necessity have employees who undertake innovative and spontaneous activities that go beyond prescribed role or job requirement (Osman et al, 2019;Mushtaq and Umar, 2015;Skarlicki and Latham, 1997).…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…Referred to as "going beyond the call of duty" or "esprit de corps" (Bolino and Turnley, 2003), OCB is initially defined as "individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system and that in aggregate promotes the effective functioning of the organization" (Organ, 1988, p. 4). Results of previous studies have suggested that, for any organization to function efficiently, it must of necessity have employees who undertake innovative and spontaneous activities that go beyond prescribed role or job requirement (Osman et al, 2019;Mushtaq and Umar, 2015;Skarlicki and Latham, 1997).…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…Khan et al, (2020) stated that Civic Virtue is often defined as a person's involvement in organizational activities. This indicator refers to the responsibility that the organization gives to a person to improve the quality of the field of work occupied (Osman et al, 2019).…”
Section: The Results Of This Study Indicate That Teachers Have High O...mentioning
confidence: 99%
“…Organizational success comes from employee involvement in OCB, which includes voluntary activity, personal discretion, and supporting coworkers outside of work hours without complaining (Kim et al, 2020;Marcos et al, 2020;Arshad et al, 2021;Notanubun, 2021). This practice promotes positive engagement without expectations (Osman et al, 2019;Potipiroon & Faerman, 2020). OCBs will impact future organizational efficiency and profitability (Massoudi et al, 2020).…”
Section: Hypothesis-research Design Relationshipmentioning
confidence: 99%
“…Work Motivation (WM) is a psychological component that motivates workers to achieve better. Well-being, attachment, happiness (Jafarpanah & Rezaei, 2020;Nurjanah et al, 2020;Bartlett et al, 2022), facilities and infrastructure (Notanubun, 2021;Zia et al, 2022), feelings of appreciation, organization, superior care, work-life balance, and supervision all have an impact on WM (Osman et al, 2019;Abdullah & Marican, 2020;Arshad et al, 2021;Abdullah & Wider, 2022). Workplace motivation boosts OCB and confidence in overcoming challenges (Abdullah & Marican, 2020).…”
Section: Hypothesis-research Design Relationshipmentioning
confidence: 99%